2021
DOI: 10.1002/alz.12313
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic conditions associated with dementia risk: The Cardiovascular Health Study

Abstract: Introduction Ophthalmic conditions and dementia appear to overlap and may share common pathways, but research has not differentiated dementia subtypes. Methods Diagnoses of cataracts, age‐related macular degeneration (AMD), diabetic retinopathy (DR), and glaucoma were based on medical histories and International Classification of Diseases, Ninth Revision (ICD‐9) codes for 3375 participants from the Cardiovascular Health Study. Dementia, including Alzheimer's disease (AD) and vascular dementia (VaD), was classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 48 publications
(107 reference statements)
1
23
0
Order By: Relevance
“…Impairments in visual acuity and visual fields have been observed more frequently in AD patients than in similarly aged individuals without AD 27,28 . Further, the presence of ophthalmic conditions, such as cataracts and age-related macular degeneration, has been found to be associated with an increased risk of all-cause dementia and AD 29 . Amyloid deposits, which have been linked to the development of AD and have been associated with the acceleration of AD progression, have been found in the lens of the eye in some individuals with age-related cataracts, potentially indicating common neuropathological pathways leading to AD and cataracts 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in visual acuity and visual fields have been observed more frequently in AD patients than in similarly aged individuals without AD 27,28 . Further, the presence of ophthalmic conditions, such as cataracts and age-related macular degeneration, has been found to be associated with an increased risk of all-cause dementia and AD 29 . Amyloid deposits, which have been linked to the development of AD and have been associated with the acceleration of AD progression, have been found in the lens of the eye in some individuals with age-related cataracts, potentially indicating common neuropathological pathways leading to AD and cataracts 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the study provides data that allowed for calculation of sample sizes for future studies related to OCT measures and determine that VFQ-25 differences are unlikely to yield important differences in future studies with groups <1,600. Another limitation is the lack of inclusion of an eye disease study group (i.e., those with AMD), which is particularly important, given the higher rate of dementia associated with AMD (20). Future studies should incorporate the use of a cognitive screening measures for the visually impaired, and inclusion of blood-based biomarkers such as beta-amyloid and tau is worth considering in future studies if sensitivity and reliability improve.…”
Section: Discussionmentioning
confidence: 99%
“…More and more animal experiments and clinical evidence have shown an epidemiological, genetic, molecular, and clinical link between AD, nAMD, and cataracts ( Baker et al, 2009 ; Tsai et al, 2015 ; Hwang et al, 2021 ). AD is the most common dementia of the elderly, wherein visual abnormalities occur before cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, AH of senile cataract patients cannot serve as the control group, because there might be a potentially important link between cataract and AD as mentioned above. For example, a population-based prospective study of 5,888 adults, aged ≥65 years, found that cataracts were associated with both AD and VAD/mixed dementia, whereas nAMD was associated with AD only ( Hwang et al, 2021 ). Based on our data, it could be speculated that cataracts and nAMD are risk factors for AD, and cataracts may be more likely to develop various types of dementia than patients with nAMD.…”
Section: Discussionmentioning
confidence: 99%